The relationship of knowledge level of class xii students with attitude to hiv/aids prevention in the same state 9 regency of tangerang 2022 - Sabda Azis, Rohmi; Taufiq, Mizwar; Karim, Abdul (Vanchapo Health Science Journal, 2023)
The existence of different levels of knowledge about sex will cause different attitudes towards sex itself, which in turn affects sexual behavior. The negative impact of free sex cannot be separated from the individual's attitude towards free sex. A high level of knowledge about HIV/AIDS can make adolescents have a positive attitude to prevent HIV/AIDS. The author is interested in conducting research on "The Relationship between Students' Knowledge Levels with HIV/AIDS Prevention Attitudes in SMA Negeri 9 Tangerang Regency". The Purpose Of The Study: To find out the relationship between the level of knowledge of class XII students and the attitude of preventing HIV/AIDS in SMA Negeri 9 Tangerang Regency in 2022. Methods: This study uses an analytical survey design using a total sampling design (total sample). The sample in this study consisted of 128 respondents using a questionnaire and the data collected would be processed or computerized. Result: of 128 respondents there were 113 respondents with good knowledge and 15 respondents with poor knowledge while 102 respondents had positive attitudes of prevention and 26 respondents had negative attitudes of prevention. Conclusion: This study shows that there is a significant relationship between knowledge and attitude of prevention of class XII students at SMA Negeri 9 Tangerang Regency with p value: 0.44.